Empowering India’s Dairy Women : A Holistic Approach Through Microfinance and SHGs - Patil, Arun Hindurao (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : The study aimed to explore the impact of microfinance and self-help groups (SHGs) on empowering women entrepreneurs in India’s dairy sector. It focused on promoting clean milk production. Methodology : The research employed a descriptive and exploratory design. Primary and secondary data were collected from various dairy communities. Data analysis included reviewing relevant literature and contextualizing findings within existing research. Findings : The study found that microfinance and SHGs significantly enhanced women’s economic empowerment and contributed to clean milk production. Access to microfinance increased household incomes and investments in sanitation. SHGs fostered collective action and improved infrastructure. Practical Implications : Integrating microfinance and SHGs was suggested to drive sustainable development in the dairy industry by empowering women entrepreneurs. Targeted training and financial literacy programs were identified as essential for maximizing these benefits. The adoption of clean milk practices could be encouraged, leading to potential increases in dairy exports in India. Originality : The study uniquely combined an examination of the roles of microfinance and SHGs in empowering women and promoting clean milk production in India’s dairy industry.